Tattoo Johnny : 3,000 tattoo designs - Tattoo Johnny (Firm) (New York : Sterling Innovation, 2010)
A collection of themed designs for tattoos.
Angels and demons --Animals --Armband, lower back and belly designs --Japanese and Asian --Butterflies and insects --Suns and moons --Dragons --Fairies --Flowers --Sea life --Patriotic and military --Pinups --Religious and spiritual --Skulls and horror --Traditional --Zodiac.
Includes index.
Keywords: Tattooing -- Pictorial works; Tattooing